The adaptation on the criminal legislation of some african states in the light of the Rome Statute - (:unkn) unknown (My University, 2019)
Signed in Rome on 17 July 1998, the Rome Statute creating the International Criminal Court entered into force on 1 July 2002 after the sixtieth ratification. The ICC is the first permanent international criminal jurisdiction to crack down on the most serious crimes that affect the entire international community. At the time of its creation, the preference was oriented towards the conventional spirit, supposed to facilitate the adhesion of the greatest number of States to this ambitious project of universal repressive justice. Coherence and realism led to the system being built on the principle of complementarity / subsidiarity. Clearly, the Court has only subsidiary jurisdiction to that of the national courts. It is only complementary to them. As a result, they retain the primacy of repression. African States that had ratified the Statute therefore had a duty to adapt national legislation - form and substance - to this international Convention. What we observe after analysis does not provide complete satisfaction. While the results differ according to the country and the method of adaptation employed, objectivity requires acknowledging that the dominant tendency has been to adapt the formal rules, to the detriment of the substantive rules.However, States - through national legislation - must improve the whole system of indirect application of international criminal law by effectively acting as the first weapon of repression. The optimal adaptation of the Statute is the one that better corresponds to the spirit of complementarity / subsidiarity in which genuine primacy is given to national jurisdiction and not a de facto primacy granted to the Court. The incorrect and superficial adaptation of national legislation unfortunately leads to the opposite. For this reason, a new reflection based on the real appropriation of the Statute must be done so that the national legislators can go to the end of the process. The future of international criminal justice
Keywords: African Research